Comparison of dengue and other febrile illnesses in patients admitted to Teaching Hospital- Peradeniya (Bangladesh Journal of Medical Science, 2021)
Background: Dengue is a severe and notifiable infection in Sri Lanka and other tropical countries.There are other febrile illnesses,which have the same symptoms as dengue. Identifying early changingmarkers in blood and their changing patterns in dengue and other febrile illnesses will help to differentiatedengue patients from other febrile illnesses.It is important for the early recovery and management of the dengue patients.Methods: Dengue suspected 288 patients were selected from adult medical wards inTeaching hospital-Peradeniya, after initial screening process. Out of whole population, 56% were RTPCRpositive for dengue and RT-PCR negative population (44%) was named as other febrile illnesses.Results of variations in liver enzymes, full blood count (FBC), demographic and hospitalization detailsin both groups were obtained from hospital records.Results: Male predominance and highly affectedyoung population were detected in both groups. Number of days from onset of fever to admission tothe hospital is lower and hospitalization period is higher in dengue than other febrile illnesses. Onadmission, higher level of aspartate transaminase, significant lymphopenia and higher mean cell volume(MCV) were noticed in dengue patients. On discharge, lower total white blood cell count, lower absolutelymphocyte count, lower platelet count and increased levels of transaminases were detected in denguecompared with other febrile illnesses.Conclusion: From dengue suspected admissions, 44% was due toother febrile illnesses which was very difficult to distinguish by symptoms of dengue. Young patients withmale predominance is common in dengue as well as in other febrile illnesses. Recovery of cytopenia inFBC and normalization of liver transaminases were lower in dengue.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.101-106